A geochronologic framework for the Ziegler Reservoir fossil site, Snowmass Village, Colorado. Issue 3 (November 2014) - Mahan, Shannon A.; Gray, Harrison J.; Pigati, Jeffrey S.; Wilson, Jim; Lifton, Nathaniel A.; Paces, James B.; Blaauw, Maarten
Abstract: The Ziegler Reservoir fossil site near Snowmass Village, Colorado (USA), provides a unique opportunity to reconstruct high-altitude paleoenvironmental conditions in the Rocky Mountains during the Last Interglacial Period. We used four different techniques to establish a chronological framework for the site. Radiocarbon dating of lake organics, bone collagen, and shell carbonate, and in situ cosmogenic 10 Be and 26 Al ages on a boulder on the crest of a moraine that impounded the lake suggest that the ages of the sediments that hosted the fossils are between ~140 ka and >45 ka. Uranium-series ages of vertebrate remains generally fall within these bounds, but extremely low uranium concentrations and evidence of open-system behavior limit their utility. Optically stimulated luminescence (OSL) ages (n = 18) obtained from fine-grained quartz maintain stratigraphic order, were replicable, and provide reliable ages for the lake sediments. Analysis of the equivalent dose (DE ) dispersion of the OSL samples showed that the sediments were fully bleached prior to deposition and low scatter suggests that eolian processes were likely the dominant transport mechanism for fine-grained sediments into the lake. The resulting ages show that the fossil-bearing sediments span the latest part of Marine Oxygen Isotope Stage (MIS) 6, all of MIS 5 and MIS 4, and the earliest part of MIS 3.